Pelatihan Pembuatan Interior Ruang Keluarga dengan Konsep Kontemporer pada Sekolah SMK (BM) Pab 3 Medan Estate - Rani Hermita; Juli Atika; Anggi Ayumi C (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The design of a family room with a contemporary concept aims to create a comfortable, functional, and aesthetic space according to the needs of the user. The contemporary concept prioritizes a simple, clean, and flexible design by combining modern materials such as glass, metal, and concrete with natural elements such as wood and stone. The selection of neutral colors is combined with bold color accents to give a dynamic impression. The layout of the room is designed to be efficient with comfortable circulation and the use of minimalist and multifunctional furniture. Natural lighting is maximized through the use of large openings, supported by warm artificial lighting to create a comfortable atmosphere. The integration of smart home technology is also applied to increase the comfort and ease of use of the space. The design results are expected to produce a family room that is modern, functional, and supports interaction between family members.